Sytuacja kobiet na europejskim rynku pracy - Rewizorski, Marek (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The considerations presented in the paper demonstrate that the situation of women in the European labor market has considerably improved over the last decade. This is facilitated, among other things, by the extensive legal instruments stipulated in the Treaty on the Functioning of the European Union and in so-called ‘equality directives’. Yet, despite this extensive and moderately coherent system of legal protection of women in the labor market, they continue to have a weaker position than men. Gender segregation in the European Union is a considerable problem; it is exemplified by women’s limited access to attractive positions and a gender pay gap, i.e. obtaining lower remuneration than men employed in comparable positions. There are also other factors that influence limited women’s activity in professional life. For a long time women have been second to men in terms of education, but the differences in this area have been gradually decreasing in recent times. What continues to be a factor to curb the participation of women in the European labor market is insufficient childcare provisions. It should be pointed out that confronting demography with employment, and requesting that women choose between home and family or work falsifies the problem. This has clearly been noted in the Europe 2020 strategy, which creates a feedback between women’s employment and their traditional role of guardians of home and hearth. This is facilitated by flexible instruments in the labor market, such as contracts typical for a flexecurity model, e.g. non-standard contracts and flexible hour contracts. Their implementation can contribute to maintaining a positive trend that has recently been manifested in an increasing rate of employed women.
The Situation of Women in the European Labor Market